The Role of the Skin Microbiome in Enhancing Acne Treatment Outcomes: A Meta-Analysis and Statistical Synthesis - Maasarji, Ryan; Al-Nawaiseh, Noura F.; Sh’yyab, Hebatallah F.; Alkhamaiseh, Sara A.; Al Zaidanin, Mohammad; Kadhim, Noor T.; Alshaer, Nour M; Khlifat, Rola Ahmad; Rawadieh, Tassnim S.; Almomani, Lina K. (Journal of Neonatal Surgery, 2025)
Acne vulgaris is a chronic inflammatory disorder of the pilosebaceous unit in which cutaneous microbiome dysbiosis plays a key role. Lesions can be ameliorated with conventional systemic antibiotics but often at the expense of perturbation of commensal communities. More effective adjunctive therapies will hopefully be newer adjunctive therapies — including probiotic treatments that try to purposefully modulate the skin microbiota. Five controlled studies (total N = 157) comparing antibiotic therapy with or without microbiome‑targeted intervention were meta‑analysed. In this PRISMA systematic search of PubMed, Embase and Scopus up to May 2025, we retrieved two cohort studies, two randomized controlled trials, and one case–control study. With negligible heterogeneity (I² = 0%), outcomes were transformed into Hedges’ g and pooled in a fixed‑effects model. To test if microbiome targeted treatments with antibiotics may lead to an improvement in severity scores compared to treatment with antibiotics alone, we pooled data from two studies and evaluated differences in the effect size (ES) using Cohen’s d, also known as Hedges’ g. Results support the inclusion of adjuncts that are microbiome‑friendly in acne management. These benefits need to be confirmed in future larger, long term trials with elucidation of the mechanisms responsible